Diffuse Optical Characterization of the Healthy Human Thyroid Tissue and Two Pathological Case Studies. - Claus Lindner; Mireia Mora; Parisa Farzam; Mattia Squarcia; Johannes Johansson; Udo M Weigel; Irene Halperin; Felicia A Hanzu; Turgut Durduran (PLoS ONE, 2016)
The in vivo optical and hemodynamic properties of the healthy (n = 22) and pathological (n = 2) human thyroid tissue were measured non-invasively using a custom time-resolved spectroscopy (TRS) and diffuse correlation spectroscopy (DCS) system. Medical ultrasound was used to guide the placement of the hand-held hybrid optical probe. TRS measured the absorption and reduced scattering coefficients (μa, μs') at three wavelengths (690, 785 and 830 nm) to derive total hemoglobin concentration (THC) and oxygen saturation (StO2). DCS measured the microvascular blood flow index (BFI). Their dependencies on physiological and clinical parameters and positions along the thyroid were investigated and compared to the surrounding sternocleidomastoid muscle. The THC in the thyroid ranged from 131.9 μM to 144.8 μM, showing a 25-44% increase compared to the surrounding sternocleidomastoid muscle tissue. The blood flow was significantly higher in the thyroid (BFIthyroid = 16.0 × 10-9 cm2/s) compared to the muscle (BFImuscle = 7.8 × 10-9 cm2/s), while StO2 showed a small (StO2, muscle = 63.8% to StO2, thyroid = 68.4%), yet significant difference. Two case studies with thyroid nodules underwent the same measurement protocol prior to thyroidectomy. Their THC and BFI reached values around 226.5 μM and 62.8 × 10-9 cm2/s respectively showing a clear contrast to the nodule-free thyroid tissue as well as the general population. The initial characterization of the healthy and pathologic human thyroid tissue lays the ground work for the future investigation on the use of diffuse optics in thyroid cancer screening.